The Effectiveness of Public Policy in Jambearum Village, Jember Regency: A Study of Village Governance - Jasmine Helwa Malika; Najah Baroud (Pravda: Social Science Interdisciplinary Journal, 2026)
Background. Village governance plays a crucial role in ensuring the successful implementation of public policies at the local level. As the governmental unit closest to the community, villages hold strategic responsibilities in delivering public services and implementing development programs aligned with citizens' needs. However, the effectiveness of public policy at the village level is often influenced by governance practices, particularly in terms of transparency, accountability, and community participation. Purpose. This study aims to analyze the effectiveness of public policy implementation in Jambearum Village, Jember Regency, with a focus on governance principles such as transparency, accountability, and public participation in village administration. Method. The study employed a descriptive qualitative approach using secondary data sources, including official village documents, statistical data from the Central Bureau of Statistics (BPS), information from the Village Information and Documentation Management Officer (PPID), and relevant policy reports. The collected data were analyzed regularly to assess policy implementation and governance practices. Results. The findings indicate that public policies implemented in Jambearum Village have been relatively effective, particularly in the areas of public service delivery and basic infrastructure development. This effectiveness is supported by community involvement through Village Consultative Meetings (Musyawarah Desa) and coordination among village institutions. Nevertheless, several challenges remain, including limited human resources capacity and insufficient evaluative documentation to support continuous improvement. Conclusion. The study concludes that policy effectiveness at the village level depends not only on appropriate planning but also on adaptive governance practices and continuous evaluation. Strengthening the capacity of village officials and enhancing community participation are essential to creating impactful and sustainable public policies that directly benefit local communities.